The SHIVA Western Pacific Campaign in Fall 2011 - Aazani, Mujahid; Nur Aleesha, Abdullah; Maznorizan, -; Nor Aieni, Haji Mokhtar (Faculty of Science, University of Malaya, 2013)
This paper briefl y summarizes the activities and observations made during the SHIVA (Stratospheric Ozone: Halogen Impacts in a Varying Atmosphere) Western Pacifi c campaign in fall 2011, here referred to as the SHIVA South China Sea (SCS) campaign. The campaign addressed investigation of emissions of so-called halogenated very short-lived substances (VSLS) from the South China Sea (SCS), their atmospheric transport and transformation, their contribution to the budget of ozone destroying halogens in the stratosphere. Key fi ndings of the SHIVA campaign are that, (a) the SCS is indeed a prominent emission region for halogenated VSLS, mostly due to the emissions of micro- and macro-algae, (b) in the boundary layer of the marine atmosphere typical VSLS mixing ratios were 3.6 – 13.3 ppt and in the upper troposphere 4.1±0.6 ppt, which may well explained a total source gas (SG) and product gas (PG) injection of [VSLS] = 4 – 5 ppt into the global stratosphere.